(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article discusses the features of the application and resolution of petitions when familiarizing with the materials of the criminal case. Familiarization of the accused and his defense counsel with the materials of the criminal case is of great importance, since it allows them to evaluate the collected evidence, file petitions for additional investigative actions, and form their position for participation in the trial.